The Collective Behavior Framework of Robert E. PARK - Aguirre, B. E. (Revista de Ciências Sociais, 2020)
Robert E. Park's. position as one of the towering founding intellects of modern social sciences is well established. He had enormous influence as a teacher at the University of Chicago and, as a thinker, his contributions to the study of urbanism and human ecology, race relations, and coflective behavior, to name just a few of his fields of interest, were dominant perspectivas at the time of their writing and continue to have resonance in the literature today. The study of collective behavior and social movements has received during the last 25 years a great deal of attention by social scientists, some of whom may be unaware of Park's earlier contributions. The intent is to offer a systematic summation of Park's conceptual framework. The first part of the paper presents Park's view of the characteristics and distinguishing features of collective behavior and the forms of collective behavior ordered in terms of their degree of institutionalization. This is followed by Park's natural history approach to the conditions of coflective behavior. The third section presents his views of the functional consequences of collective behavior for social adaptation . The paper concludes with an evaluation of his framework.